Case report: Subjective loss of performance after pulmonary embolism in an athlete– beyond normal values. Issue 1 (December 2016) - Dumitrescu, Daniel; Gerhardt, Felix; Viethen, Thomas; Schmidt, Matthias; Mayer, Eckhard; Rosenkranz, Stephan
Abstract Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a progressive disease. For patients with operable CTEPH, there is a clear recommendation for surgical removal of persistent thrombi by pulmonary endarterectomy (PEA). However, without the presence of PH, therapeutic management of chronic thromboembolic disease (CTED) is challenging - especially in highly trained subjects exceeding predicted values of maximal exercise capacity. Case presentation A 43-year-old male athlete reported with progressive exercise limitation since 8 months. Six months earlier, pulmonary embolism had occurred, and was treated since with oral anticoagulation. A pulmonary ventilation/perfusion scan showed severe ventilation/perfusion mismatch: chest CT and pulmonary angiography revealed bilateral wall-adherent thrombotic material, but pulmonary hemodynamics were completely normal. His peak oxygen uptake exceeded predicted values, however exercise ventilatory efficiency was abnormal, compared to a matching athlete. After thoroughly discussing therapeutic options with the patient, he successfully underwent pulmonary endarterectomy at an expert center. Five and twelve months after surgery, his maximal exercise capacity and ventilatory efficiency profoundly improved beyond preoperative values, and his subjective exercise tolerance had returned to normal. Conclusions Significant CTED may be present without relevant pathologic changes in pulmonary hemodynamics at rest. Reaching normal values of maximal exercise capacity does not exclude pulmonary vascular disease in highly trained subjects. More data are needed to evaluate the risk-/benefit ratio of PEA in patients with CTED and normal pulmonary hemodynamics. A thorough discussion with the patient as well as shared decision making regarding therapy are mandatory. Cardiopulmonary exercise testing may add important clinical information in the non-invasive diagnostic evaluation at baseline and during follow-up.